ANALISIS SURVEY FAKTOR PENYEBAB PERNIKAHAN DINI DAN EKSISTENSI BUDAYA MERARIQ KODEK PADA REMAJA DI LOMBOK TIMUR - Aulia, Fitri; Suastra, I Wayan; Aryana, Ida Bagus Putu (JKP (Jurnal Konseling Pendidikan), 2023)
Early marriage is a social problem that is still relevant in Indonesia, including in NTB Province. Especially in East Lombok Regency, Terara District. This research aims to identify the factors that cause early marriage and the existence of the codek-drawing culture among teenagers in Terara. The method used is a quantitative approach, survey method, data was collected from a population of female teenagers who were perpetrators of early marriage in Lando Village, Terara District with a sample of 49 respondents. The techniques used in this research are questionnaires and interviews. The results showed that of the 49 respondents who filled in the 21 question items, 278 respondents chose the score "Strongly Agree (SS)," 376 respondents chose "Agree (S)," 283 respondents chose "Disagree (TS)," and 92 respondents select "Strongly Disagree (STS)." This shows that the factors causing early marriage are (1) educational background, (2) promiscuity, (3) customs and culture, (4) family economy, (5) mass media, and (6) parental encouragement influencing decision making. early-age marriage. Among these factors, the existence of the Merariq Kodek culture is still quite dominant, through parental encouragement which is still strong towards the existence of this culture.